Prevalence of chronic obstructive pulmonary disease in the global population with HIV: a systematic review and meta-analysis - Jean Joel Bigna, MD; Angeladine Malaha Kenne, MPH; Serra Lem Asangbeh, MPH; Aurelie T Sibetcheu, MD (Elsevier, 2018)
Background: In recent years, the concept has been raised that people with HIV are at risk of developing chronic obstructive pulmonary disease (COPD) because of HIV infection. However, much remains to be understood about the relationship between COPD and HIV infection. We aimed to investigate this association by assessing studies that reported the prevalence of COPD in the global population with HIV. Methods: In this systematic review and meta-analysis, we assessed observational studies of COPD in people with HIV. We searched PubMed, Embase, Web of Science, and Global Index Medicus, with no language restriction, to identify articles published until June 21, 2017, and we searched the reference lists of the retrieved articles. Eligible studies reported the prevalence of COPD or had enough data to compute these estimates. We excluded studies in subgroups of participants selected on the basis of the presence of COPD; studies that were limited to other specific groups or populations, such as people with other chronic respiratory diseases; and case series, letters, reviews, commentaries, editorials, and studies without primary data or an explicit description of methods. The main outcome assessed was prevalence of COPD. Each study was independently reviewed for methodological quality. We used a random-effects model to pool individual studies and assessed heterogeneity (I2) using the χ2 test on Cochrane's Q statistic. This study is registered with PROSPERO, number CRD42016052639. Findings: Of 4036 studies identified, we included 30 studies (151 686 participants) from all WHO regions in the meta-analysis of COPD prevalence. 23 studies (77%) had low risk of bias, six (20%) had moderate risk of bias, and one (3%) had high risk of bias in their methodological quality. The overall prevalence of COPD was 10·5% (95% CI 6·2-15·7; I2=97·2%; six studies) according to the lower limit of normal definition of COPD, and 10·6% (6·9-15·0; 94·7%; 16 studies) according to the fixed-ratio definition. COPD prevalence was higher in Europe and among current and ever smokers, and increased with level of income and proportion of participants with detectable HIV viral load. Prevalence of COPD was significantly higher in patients with HIV than in HIV-negative controls (pooled odds ratio 1·14, 95% CI 1·05-1·25, I2=63·5%; 11 studies), even after adjustment for tobacco consumption (2·58, 1·05-6·35, 74·9%; four studies). Interpretation: Our findings suggest a high prevalence of COPD in the global population with HIV, and an association with HIV. As such, COPD deserves more attention from HIV health-care providers, researchers, policy makers, and stakeholders for improved detection, overall proper management, and efficient control of COPD in people with HIV. Efforts to address this burden should focus on promoting the decrease of tobacco consumption and adherence to highly active antiretroviral therapy to reduce viral load. Funding: None.